The effect of fat and coffee concentration on the consumer acceptance of iced‐coffee beverages. Issue 11 (15th October 2021) - Mahmud, M M Chayan; Shellie, Robert A.; Mohebbi, Mohammadreza; Mahato, Dipendra Kumar; Keast, Russell
Abstract : Abstract: The fat content of a product has the potential to influence consumer liking via mouthfeel, taste, and aroma modification. This study aims to determine the effects of fat and coffee concentration on sensory attributes and consumer liking of iced‐coffee beverages. Nine iced‐coffee beverages were formulated: low fat–low coffee; medium fat–low coffee; high fat–low coffee; low fat–medium coffee; medium fat–medium coffee; high fat–medium coffee; low fat–high coffee; medium fat–high coffee; and high fat–high coffee. Fat content was adjusted using different concentrations of cream, and coffee using different concentrations of Nescafé Blend 43. Regular coffee consumers ( n  = 231) rated their overall liking using a 9‐point hedonic scale and completed a ranked preference based on degree of liking of all samples. Consumers also rated liking for sensory attributes: appearance, aroma, sweetness, coffee intensity, mouthfeel, and aftertaste. There were significant relationships between 1/ fat and 2/ coffee and liking of iced‐coffee beverages ( p  < 0.001). There were three clusters of consumers based on iced‐coffee preferences. Response surface curve indicated that overall liking of iced‐coffee beverages increased with the increase of fat and coffee concentration to a certain level, then continuing to increase the fat and coffee concentration decreases overall liking. The finding of this study provides valuable information on how fat and coffee concentrations can be adjusted to modify consumer acceptance of iced‐coffee beverages. Practical Application: The results of this research could be applied to reformulate iced‐coffee beverages, while ensuring consumer acceptance. In addition, this research provides evidence that sweetness, aftertaste, coffee‐intensity, and mouthfeel are important sensory attributes associated with consumer liking of iced‐coffee beverages.